2021
DOI: 10.1186/s13020-021-00493-4
|View full text |Cite
|
Sign up to set email alerts
|

Traditional herbal formula Wu-Mei-Wan alleviates TNBS-induced colitis in mice by inhibiting necroptosis through increasing RIPK3 O-GlcNAcylation

Abstract: Background Accumulating evidence indicated that necroptosis plays an essential role in the pathogenesis of inflammatory bowel disease (IBD). The O-linked β-N-acetylglucosaminylation (O-GlcNAcylation) of necroptotic signal molecule receptor-interacting serine-threonine kinase 3 (RIPK3) was reported to exert a protective effect in gut inflammation. Our recent study suggested traditional Chinese herbal formula Wu-Mei-Wan (WMW) as an effective prescription in mouse colitis. However, the potential m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Cells undergoing necroptosis exhibit disrupted cell membranes, which is the major difference from necrosis. The RIPK3 and its substrate MLKL play critical roles in the formation of necroptosis [ 99 101 ]. In acute ischemic kidney injury, the expression of acyl-CoA synthetase long-chain family member 4 (ACSL4, a key enzyme in ferroptosis) is increased and is correlated with the severity of renal damage [ 82 , 102 ].…”
Section: Ferroptosis-related Biological Response In Akimentioning
confidence: 99%
“…Cells undergoing necroptosis exhibit disrupted cell membranes, which is the major difference from necrosis. The RIPK3 and its substrate MLKL play critical roles in the formation of necroptosis [ 99 101 ]. In acute ischemic kidney injury, the expression of acyl-CoA synthetase long-chain family member 4 (ACSL4, a key enzyme in ferroptosis) is increased and is correlated with the severity of renal damage [ 82 , 102 ].…”
Section: Ferroptosis-related Biological Response In Akimentioning
confidence: 99%
“…As a traditional Chinese medicine (TCM), WMP is widely used to treat digestive system diseases in clinical practice in China [40]. Previous studies showed that WMP had extensive pharmacological effects, including alleviated trinitrobenzenesulfonic acid-(TNBS-) induced colitis [41], prevented high-fat diet-induced obesity [42], protected pancreatic β cells [43], and reduced insulin resistance [44]. Noteworthy, WMP can treat roundworm coldness in the extremities and longtime diarrhea of cold-heat complex type based on the "Treatise on Febrile Disease."…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no record of CAC in TCM literatures, however, according to its clinical characteristics and pathogenesis, CAC can be classified as a category of "dysentery" and "risceral intoxication." WMP is a famous formula, which is composed of ten herbs: Fructus Mume, Herba Asari, Rhizoma Zingiberis, Rhizoma Coptidis, Radix Angelicae sinensis, Rhizoma Typhonii gigantei, Pericarpium Zanthoxyli, Ramulus cinnamomi, Radix Ginseng, and Cortex Phellodendri [41]. Many preclinical and clinical trials found that WMP was suitable for the early prevention and treatment of inflammatory bowel disease and CAC.…”
Section: Introductionmentioning
confidence: 99%
“…WMW, a traditional medicine in China, has been used to treat chronic intestinal inflammatory disorders for two millennia. Recent studies have found that WMW significantly reduces the acute colonic inflammatory response induced by trinitrobenzenesulfonic acid by reducing the infiltration of macrophages and neutrophils and the levels of local IL-1 β , IL-6, TNF- α , and IFN- γ ( Wu F. et al, 2021 ). UC is a chronic inflammatory disorder, and DSS is commonly used to induce UC in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of evidence shows that WMW has anti-colon necrosis and anti-intestinal fibrosis effects and can inhibit intestinal inflammation and repair damaged intestinal mucosa. However, the specific effector mechanism(s) of WMW in the treatment of UC are not clear ( Wu et al, 2020a ; Jiang et al, 2020 ; Wu F. et al, 2021 ). WMW is made from 10 plants, including smoked plum, wild ginger (Asarum sieboldii), ginger (Zingiber officinale), Aconitum carmichaelii, Zanthoxylum, Cinnamomum cassia, Coptis chinensis, Phellodendron amurense, Panax ginseng, and Angelica sinensis.…”
Section: Introductionmentioning
confidence: 99%